PERCEIVED RISK OF VICTIMISATION AMONG INDIVIDUALS RESIDING IN CRIME HOTSPOT AREAS - Tharshini, N. K. (Publications International Lahore, Pakistan, 2022)
Perceived risk of victimisation has been studied in relation to different types of crime, neighbourhood disorder, concentrated disadvantage, and urbanity. Echoing to this notion, this research was carried out to identify the perceived risk of victimisation among individuals residing in crime hotspot areas in Sarawak, Malaysia. Data was quantitatively collected among 365 respondents from three districts namely Kuching, Sibu, and Miri. The result of the study shows that majority of the respondents are highly afraid of sexual abuse, physical abuse, house breaking, theft, and fraud. It is deemed important to identify the perceived risk of victimisation among individuals residing in crime hotspot areas; thus, the predictors of contextual risk factors can be identified to propose crime prevention strategies that target vulnerable groups within the community.